Intravenous Low-Dose Ketamine Provides Greater Pain Control Compared to Fentanyl in a Civilian Prehospital Trauma System: A Propensity Matched Analysis. (2nd January 2019) - Bronsky, E. Stein; Koola, Catherine; Orlando, Alessandro; Redmond, Diane; D'Huyvetter, Cecile; Sieracki, Heather; Tanner, Allen; Fowler, Ray; Mains, Charles; Bar-Or, David
Abstract: Objective : A few studies report comparable analgesic efficacy between low-dose ketamine and opioids such as morphine or fentanyl; however, limited research has explored the safety and effectiveness of intravenous low-dose ketamine as a primary analgesic in a civilian prehospital setting. The objective of this study is to compare pain control between low-dose ketamine and fentanyl when administered intravenously (IV) for the indication of severe pain.Methods : This was a retrospective, observational review of prehospital adult patients (≥18 years) who presented with severe pain (numeric rating scale, 7–10) and were treated solely with either low-dose ketamine IV or fentanyl IV between January 1, 2014 and December 31, 2016. Propensity matched analysis was performed adjusting for all baseline variables with p ≤ 0.10 and for baseline pain score to match ketamine and fentanyl patients on a one-to-one ratio. The primary outcome was change in pain score from baseline to after treatment and evaluated with a paired t-test. Secondary outcomes were changes in vital signs and Glasgow coma scale (GCS) from baseline to after treatment, as well as incidence of clinically significant adverse events (AEs); AEs were followed from scene arrival through emergency department discharge.Results : Propensity matched analysis produced 79 matched pairs. Ketamine IV patients, receiving a mean (SD) dose of 0.3 (0.1) mg/kg, showed a significantly larger mean decrease in pain after treatment, compared to the fentanyl IV patients (−5.5 (3.1) vs. −2.5 (2.4), p < 0.001). A significantly greater proportion of patients receiving ketamine IV achieved at least a 50% reduction in pain compared to those receiving fentanyl IV (67% vs. 19%, p < 0.001), marking 52 ketamine IV patients as responders to treatment. Vital signs demonstrated a nonsignificant decrease in blood pressure, respiratory rate, heart rate, and GCS. No clinically significant AEs were reported for patients receiving ketamine IV.Conclusion : The significant reduction in pain, significantly high proportion of ketamine responders, and the lack of clinically significant AEs characterizing patients receiving low-dose ketamine IV compared to fentanyl IV, all provide further support for its use as an effective prehospital analgesic.Level of Evidence : Level III, therapeutic.